Kompleksitas Kepemimpinan Kristen Antargenerasi Dalam Konteks Kontemporer - Heintje Barry Kobstan; Markus Lewi Sasonto (Jurnal Penggerak, 2023)
The main objective of this work is to show the complexity of intergenerational leadership in a contemporary context. Through indepth research and analyzing differences and similarities between different generations in terms of views, values, and attitudes, as well as identifying effective strategies and approaches to address these challenges. This research also aims to identify key factors influencing dynamics between different generations and formulate approaches that can be used to address new challenges. This research looks at generational differences not only from the perspective of conflict but also from the perspective of working together and using different values to achieve common goals. In this study, literature studies and journals were used as methods related to the analysis of relevant and current literature on intergenerational Christian leadership issues. This approach enables a deep understanding of the complexities and dynamics that exist in the context of intergenerational Christian leadership in the current situation. In discussing the leadership gap between generations in the contemporary context, it does not escape to talk about generation theory and transformational leadership theory. Generation theory and transformational leadership theory are the link and can be the answer to the leadership gap between today's generations. It is undeniable that there are differences in the opinions of the older generation about the younger generation and vice versa in the opinions of the younger generation about the older generation, causing tensions and solutions to the problem. The critical point of human interaction is related to the basic ideas, life goals, ambitions, and beliefs of the transformational leader, who will be able to bring change to the people he leads so as to bring change in serving better, holding fast to the values of truth, and encouraging and inspiring others to have confidence when working or serving and being in the life of Christ.